COMPARISON OF TWO DEFINITIONS (p-RIFLE AND KDIGO) FOR PREVALENCE OF ACUTE KIDNEY INJURY AND IN HOSPITAL MORTALITY IN A PAEDIATRIC INTENSIVE CARE UNIT OF PAKISTAN - Usman, Parveen; Qaisar, Habib; haque, Anwar ul; Abbas, Qalab (Journal of Ayub Medical College Abbottabad, 2022)
Background: To compare the Paediatric RIFLE (p-RIFLE) and Kidney Disease Improving Global Outcomes (KDIGO) definitions of acute kidney injury (AKI) for frequency of (AKI) and in-hospital mortality in critically ill children. Methods: Retrospective review of medical records of all patients (aged 1 month - 16 years) admitted in Paediatric Intensive Care Unit from January 2015-December 2016, with length of stay >48 hours, was done. Patients with chronic kidney disease were excluded. Receiver operating characteristic (ROC) curves were used to evaluate the performance of the p-RIFLE and KDIGO criteria to predict the AKI related mortality. Logistic regression analysis was done to determine the association of different variables with mortality in AKI patient based on p-RIFLE, KDIGO. A p-value of <0.05 was considered significant. Results: Out of total 823 patients admitted during the study period, 562 patients were included in the study. Median age was 2 years (Interquartile range 8 years). AKI frequency according to p-RIFLE and KDIGO were 391 (70%), and 372 (66%) respectively. Overall, 106/823 (12.8%) children died during study period, 78 (19.9%) in AKI by p-RIFLE and 76 (20.4%) in AKI by KDIGO died. The area-under- curve for in-hospital mortality for p-RIFLE and KDIGO criteria were 0.525 (p=0.427), and 0.534 (p=0.276), respectively. Conclusion: P-RIFLE is more sensitive compared to KDIGO in diagnosing AKI in critically ill children; identifying a greater number of moderate staged AKI cases. Greater AKI severity is associated with higher mortality in critically ill children.